Lobbying in the EU: prospects and challenges of the mandatory transparency register - Ridao Martín, Joan; Araguàs Galcerà, Irene (Frontiers in Political Science, 2025)
Lobbying practice is an essential part of the decision-making process in the European Union. The promotion of the practice of lobbying in institutions of the European Union quite naturally raised the question of regulating this activity according to the standards that arise from the EU-founding treaties and the Charter of Fundamental Rights of the European Union. The European Parliament and the European Commission set up in 2021 the EU Transparency Register through an interinstitutional agreement, later joined by the Council. The interinstitutional agreement of 2021 states a mandatory register system to eliminate the deficiencies of the voluntary system and provide additional registration incentives. A big role for improving of lobbying regulations has been played by the Court of Justice of the European Union. In recent years, the ultimate interpreter of European law has passed several judgments that set lobbying activities boundaries and the rules applicable to conflict-of-interest situations. The objective of this work is to analyse the regulation and operation of the EU Transparency Register and the most relevant jurisprudential pronouncements as well as the prospects and challenges of the mandatory system recently implemented.